Workers’ Participation in Management in Nepal - Lamichhane, Bimal Prasad (Kalika Journal of Multidisciplinary Studies, 2021)
Worker’s participation in management is a system of collective formal or informal communication and joint consultation between employer and employee individually or collectively by which workers of an organization are kept informed about the activities and actions of an undertaking and through which they communicate their view and ideas as well as contribute for management decisions of the organization where they work. It refers to any arrangement which is designed to involve workers in the important decision making within the workplace. It comprises giving scope for workers to influence the managerial decision-making process at different levels by various forms in the organization. It allows for worker’s involvement in the initiation, formulation and implementation of decisions within the organization. Worker participation is important component to enhance human resource development in modern organizations. In the modern time worker’s participation in management became the foundation and pre-requisite for the successful operation of the organization. Participative management in the organization contributes decreasing the communication gap between the management and the workers, improve performance and productivity, lower costs, motivation, satisfaction of psychological, social, economic, self-fulfillment needs, reduction of organizational conflicts, industrial peace and stability, an ideal working environment in the organization and job satisfaction of the workers. It provides workers a sense of importance, pride, freedom, and opportunity for self-expression, a feeling of belongingness so as to create positive condition for organizational relation. The existing constitutional and legal provisions are insufficient for the protecting, safeguarding the workers right and ensuring as well as regulating the worker’s participation in management.